Evaluating descriptive and clinical characteristics of type 2 diabetes mellitus patients with physical and environmental barriers to exercise - Lohana, Chander Kumar; Kumar , Vinod (International Journal of Research in Medical Sciences, 2023)
Background: Exercise is critical in the treatment of Type 2 diabetes mellitus. It is critical to identify exercise barriers in non-exercising T2DM patients. The present study aimed to evaluate the physical and environmental barriers among non-exercising T2DM patients attending a tertiary care hospital in Karachi, Pakistan. Methods: A cross-sectional study was conducted by recruiting patients from Family Medicine outpatient clinics at the Agha Khan University Hospital from October 2018 to April 2019. Patients between the ages of 18 and 65 who had T2DM for at least six months and exercised for fewer than 150 minutes per week or 30 minutes per day were enrolled. Barriers to exercise like physical (pain/discomfort, too overweight, co-existing illness) and environmental (too hot or cold weather, unavailability or no convenient place to exercise) were observed. The Chi-square test was used for inferential statistics. Results: Of 275 patients, mean age of the patients was 46.58 ±10.96 years. There were 146 (53.1%) males and 129 (46.9%) females. Pain and physical discomfort 110 (40%) was the most common physical barrier. Moreover, hot or cold weather was reported in 48 (17.5%) patients, no convenient or nearby place to exercise in 53 (19.3%), unavailability of parks/gym in 48 (17.5%), and environmental barriers like traffic in 35 (12.7%). Conclusions: A variety of physical and environmental barriers were discovered in this study; therefore, implementing suitable therapy to overcome these barriers will allow patients to engage in physical activities that will help them control their diabetes.